Strategi Guru dalam Menangani Siswa dengan Gangguan Konsentrasi di Kelas IV SDN 4 Godong - Fenna Erisetiana Nadela Asagie; Murfiah Dewi Wulandari (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Concentration disorders are one of the common obstacles experienced by elementary school students and have a direct impact on the quality of both the learning process and learning outcomes. This study aims to describe teacher strategies in addressing concentration problems in fourth-grade students at SDN 4 Godong. The approach used was descriptive qualitative, with the research subjects being a class teacher and three students identified as having concentration problems. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that students' concentration problems emerged in two forms: social factors and cognitive factors. Students with social factors were easily distracted by conversations from their deskmates, especially due to the daily seating rotation system. Interestingly, one student focused better when sitting next to a student of the opposite gender. Meanwhile, cognitive problems were seen in students who paid attention to the teacher but required re-explanations and often fell behind during practice. The teacher implemented a drill strategy to train focus and evaluate student understanding. This strategy proved effective for students with social problems, but required a combination of additional support for students with comprehension difficulties. These findings emphasize the importance of seating arrangements and the selection of contextual learning methods.